Tropospheric Role in the Predictability of the Surface Impact of the 2018 Sudden Stratospheric Warming Event - González-Alemán, Juan J.; Grams, Christian M.; Ayarzagüena, Blanca; Zurita-Gotor, Pablo; Domeisen, Daniela I. V.; Gómara, Iñigo; Rodríguez-Fonseca, Belén; Vitart, Frédéric (Geophysical Research Letters, 2023)
Abstract Sudden stratospheric warmings (SSWs) can have a strong impact on the troposphere. Their fingerprint is often associated with the negative phase of the Northern Annular Mode (NAM) and the North Atlantic Oscillation (NAO), and extreme weather with high societal impact. However, the mechanisms behind this downward impact are not well understood. We investigate this surface impact through its associated predictability limits, by studying the 2018 SSW event. We search for predictability barriers that occurred after the onset of the SSW and before its surface impact. It is found that dynamical tropospheric events consisting of two cyclogenesis events were the main reasons for these predictability barriers in the prediction of negative NAM/NAO anomalies reaching the surface. This work corroborates that individual synoptic events might constitute predictability barriers during the downward impact of SSW events, and thereby sheds light on stratosphere-troposphere coupling. Plain Language Summary Sudden stratospheric warmings (SSWs) can have a strong impact on near-surface weather. They have the potential to alter the atmospheric circulation and associated extreme events, thus affecting society. However, the way the stratosphere couples with surface weather is not fully understood. In this work, we investigate this relationship by analyzing the predictability of the surface impact of a stratospheric warming event that occurred in 2018, and which left widespread societal impacts over Europe due to a severe cold spell and extraordinary rainy and windy conditions. We find that the impact of this SSW event on the surface was regulated by two low-pressure systems that developed over the North Atlantic. Even though the SSW event was well developed, alternative behavior of these systems could have led to drastically different weather conditions over Europe. Thus, this study highlights the role of the tropospheric circulation in the effectiveness of the stratospheric impact on surface weather. Acknowledgments JJGA is ...